Proven solutions for improving health and lowering health care costs - Pegels, C. Carl (Emerald Publishing Limited : Information Age Pub., 2003)
The purpose of this book is to convince administrators and providers of health care that scientific research has produced numerous tools, techniques, and approaches for managing health services that are most effective and most efficient. Convincing the managers and administrators of this fact is accomplished by presenting numerous easy-to-understand summaries of the research reported in the scientific research journals available at University and main city libraries.
Keywords: Health services administration.; Medical -- Health Care Delivery.; Social welfare and social services.; Health systems and services.; elektronické knihy; electronic books